The Mechanical Properties of Fly Ash and Slag Geopolymer Mortar with Micro Steel Fibers - Amouri, M. S.; Fawzi, N. M. (Engineering, Technology & Applied Science Research, 2022)
In this study, experimental mortar combinations with 1% micro steel fibers, were examined to create geopolymer mortars. To test the effect of the fibers on the mortar’s resistance, the geopolymer mortar was designed with various proportions of more environmentally friendly materials fly ash and slag. The percentage of fly ash by weight was 50, 60, and 70% of the slag. The best results were obtained when a 50:50 ratio of fly ash and slag were mixed with 1% micro steel fibers. The results showed that the mixtures containing fibers performed better in the considered tests (toughness index, ductility index, and resilience index). In the impact resistance test, the mixture contained 50% fly ash by weight of the slag with a temperature of 240°C and a curing period of 28 days, with and without micro steel fibers. Water absorption test results and void content increased when adding micro steel fibers after 7 and 28 days of curing at 24°C.